The Role of Artificial Intelligence In Enhancing Financial Decisions - Khalid Khider (Indonesian Journal Publisher, 2026)
The current research aims toanalyses the role of artificial intelligence in enhancing financial decisions, the increasing integration of Artificial Intelligence (AI) in the financial sector has revolutionized decision-making processes, offering unprecedented precision, speed, and efficiency. This paper aims to provide a comprehensive overview of AI's applications in financial decision-making, exploring its benefits and challenges. This study employed a descriptive-analytical approach, reviewing literature and previous studies related to artificial intelligence applications in the financial field. It also analyzed applied models for using machine learning algorithms in financial market forecasting and risk assessment. Furthermore, available data on the performance of AI-based systems compared to traditional financial decision-making methods were analyzed. This study explores the transformative role of AI in financial decision-making, highlighting its impact on investment strategies, risk management, and financial forecasting. AI-powered algorithms, such as machine learning and deep learning models, have enabled financial institutions to analyze vast amounts of data in real time, providing insights that were previously unattainable. These technologies facilitate enhanced predictive analytics, enabling more informed investment decisions, portfolio optimization, and asset management. The study results showed that using artificial intelligence (AI) technologies significantly improves the accuracy of financial forecasts, reduces risk levels, and accelerates decision-making by analyzing large amounts of data in a short time. The results also indicated that relying on intelligent systems helps institutions uncover hidden financial patterns, improve portfolio management, and enhance the efficiency of financial planning. However, the study pointed to some challenges associated with implementing AI, such as the need for advanced technological infrastructure and ensuring data protection.